Primary Reconstruction of Fingernail Injuries in Children with Split-Thickness Nail Bed Grafts - Rohard, Imke; Subotic, Ulrike; Weber, Daniel Max (European Journal of Pediatric Surgery, 2012)
Introduction Failure to detect and treat partial or complete avulsions of the nail bed may lead to severe nail deformity that predisposes to repeat injuries and is cosmetically inacceptable. Treatment of these injuries with split-thickness nail bed grafts (STNBGs) is controversial and no pediatric series has been published.Methods A retrospective, single center case series of nine fingers with complex nail bed injuries that were reconstructed primarily with STNBGs was performed. Surgical outcome and patient satisfaction were assessed.Results For six nail bed reconstructions, the nail bed graft was harvested from the injured finger, and for the remaining three from the great toe. Harvesting of the great toe's nail bed could be performed without removal of the nail plate by only lifting it up distally. Insufficient vascularization required primary flap coverage in six cases with three Moberg flaps, two palmar V-Y flaps, and one thenar flap. No flap was lost and all nail bed grafts had a 100% take. Only one patient required reoperation due to a hook- and split-nail deformity. All other patients were satisfied or very satisfied and the surgical outcome was least satisfactory in all but two patients.Conclusions Primary reconstruction of complex nail bed injuries with STNBGs usually gives good cosmetic and functional results in children and prevents secondary nail growth disturbances reliably.
Keywords: fingernail; nail bed transplantation; split-thickness nail bed graft; nail bed injury